Nutritional Status of the Elderly Living in Nursing Homes in Sabzevar, Iran - Reza Shahabi; Ahmad Mozaffari Jovein; Nasrin Mostofi Asl (Golestan University Of Medical Sciences, 2019)
Background and objectives: Despite the importance of physiological changes that occur in the aging process, monitoring the nutritional status of the elderly has been neglected in developing countries. Nutrition has a significant impact on the quality of life and risk of morbidity and mortality among the elderly. In this study, we evaluated nutritional status of older people living in nursing homes in Sabzevar, Iran. Methods: This descriptive cross-sectional study was conducted on 120 randomly selected elderly men (n=60) and women (n=60) living in nursing homes in Sabzevar, Iran. Data were collected using a demographic survey and the standard Mini Nutritional Assessment (MNA) questionnaire. The collected data were analyzed using SPSS16 software at significance level of 0.05. Results: Mean age of men and women was 65.4 ± 7.4 and 73 ± 7.3 years, respectively. There was a positive correlation between age and malnutrition in the elderly (P=0.013). Moreover, malnutrition was associated with gender in a way that women were more likely to suffer from malnutrition. Conclusion: Our results indicate that the nutritional status of the studied population of the elderly is poor, which needs to be urgently addressed by healthcare policymakers.